Genetic analysis of fenugreek (Trigonella foenum-graecum) accessions using morphometric and ISSR markers - RANDHAWA, GURINDER JIT; SINGH, MONIKA; GANGOPADHYAY, K K; KUMAR, GUNJEET; ARCHAK, SUNIL (The Indian Journal of Agricultural Sciences, 2012)
In a pilot study, as a prelude for characterization of the entire Trigonella germplasm conserved in the National Gene Bank, National Bureau of Plant Genetic Resources, New Delhi, genetic relatedness among a selection of 49 accessions of fenugreek (Trigonella-foenum-graecum L.) was assessed using 19 morphometric and 186 inter-simple sequence repeat (ISSR) markers. An accession of T. corniculata L. was also assessed as an out-group. The accessions were collected from different eco-geographical sites located in the states of Andhra Pradesh, Himachal Pradesh, Jammu and Kashmir, Madhya Pradesh, Uttar Pradesh, Uttarakhand, Rajasthan, Gujarat, Manipur and Bihar; and one of the accessions was imported from Eritrea. Data for 12 qualitative and seven quantitative morphometric descriptors were recorded. Significant differences within the accessions were found for all the quantitative descriptors except primary branches and seeds/pod. Shannon- Wiener Diversity Index revealed substantial diversity for all the quantitative descriptors. The morphometric data differentiated the fenugreek accessions into two clusters (at 65% similarity). A total of 100 ISSR primers were used for initial screening, out of which only 21 primers were found polymorphic. ISSR analysis was performed with selected 21 primers to generate 186 amplicons, of which 92.4% were polymorphic. Cluster analysis put 47 accessions in a single group at 65% similarity. Though there was no agreement between the groupings based on morphometric and ISSR markers (Mantel statistic 0.096), specific cases of geographic groupings were supported by both the markers. Phylogenetic positioning of the accessions with no passport information was found to be possible. The ISSR markers complemented the morphometric data in understanding the genetic divergence among the fenugreek accessions.